Potential of Dragon Blood Resin as a Complementary Therapy in Managing Sickle Cell Disease - Ghirke, Ashvini Ingle (Journal of Neonatal Surgery, 2025)
The hereditary blood condition Sickle Cell Disease (SCD) shows itself through aberrant hemoglobin that creates red blood cells to appear like crescents or sickles. The malfunctioning of vascular structures due to this structural change leads to painful sickle cell crises alongside a heightened danger of organ issues and stroke and ongoing medical conditions. The current medical treatments for SCD including hydroxyurea therapy and blood transfusions do not satisfy the complex requirements of the disease particularly when healthcare access is limited to resource-constrained areas. The need for alternative treatments using natural remedies has become more prominent as people seek Complementary and Alternative Medicine (CAM) as an additional approach to standard medical treatment of SCD. Dragon Blood Resin (DBR) stands out as a notable natural remedy because it emerges from Dracaena and Croton plant genera and multiple societies employ this resin for medicinal benefits. People who experience SCD might receive benefit from DBR because it exhibits anti-inflammatory abilities and antioxidant properties and wound-healing effects during times where persistent inflammation and oxidative stress symptoms persist. The therapeutic effectiveness of DBR develops from its ability to influence these disease-causing pathologies. Several studies reveal that Drinkwell Tree Roots (DBR) contains four essential compounds including flavonoids, alkaloids, tannins and phenolic acids that demonstrate powerful antioxidant and anti-inflammatory properties. The compounds contained in DBR might decrease oxidative damage in patients and support the healing process through inflammation control as well as the treatment of chronic ulcers which commonly affect those with SCD. Excessive oxidative stress in SCD produces red blood cell destruction that starts an inflammatory reaction which worsens disease symptoms. DBR shows strong antioxidant function that counteracts oxidative pressure through free-radical inactivation and simultaneously uses anti-inflammatory mechanisms to reduce pro-inflammatory cytokines linked to blood vessel blockade and pain attacks. DBR demonstrates potential as an effective treatment for chronic leg ulcers associated with SCD since it facilitates wound healing processes. The combination of easy availability and cost-effectiveness and environmental sustainability of DBR makes it suitable as a medical treatment alternative for people who cannot access expensive pharmaceutical drugs through limited resources. Scientific evidence regarding the efficacy and safety of using DBR for SCD treatment is currently scarce despite the traditional medical practices and phytochemical evaluation of the plant. Randomized controlled trials represent the future direction for determining the therapeutic strength of DBR as an SCD treatment and its potential role in current clinical practices. DBR needs thorough clinical assessment because such research could lead to better life quality for SCD patients in regions with limited resources.